The Anthropology of Enthnationalism: The Politics of Difference - Pokhrel, Krishna Prasad (Patan Prospective Journal, 2022)
Along with the emergence of Maoist-insurgency in Nepal ethnic awareness pervaded through the society which advanced to the form of movement even it delivered a sharp stroke at the threshold of Constitutional assembly and till it is under tide passion. The project of nation state (re)structuring of federal Nepal is on the progress. This enterprise essentially demands for some common consensus in understanding the contested notions behind the politics of identity versus difference vis-a-vis ethnic nationalism or a liberal concept of civic state before venturing the most controversial debate in searching the federal-strands in order to form a consolidated nation state. Constitutional assembly and the major political parties found largely engaged with talking about people’s ethnicity, their culture and languages as the major constructive principles pivoting around at which the federal nations were conceived. While the constitution of Nepal was announced without identification of its federal provinces because of these undercurrent emotions. Ethnic classifications are rather arbitrary, they are changing over time - today's ethnicities are yesterday’s races, and they are different in different countries. While the dubiety on those dimensions to the extent of their nature of fluidity and situational applicability may supply sufficient ground for a clear-cut demarcation of a territorial boundary for any ethnic groups in Nepal. It is equally important to remind to this detail that how the globalized forces of hybridization is taking place. Hybridization is considered a powerful blurring process through which the elements of ethnicity, identity and purity with their boundary limitation becomes indistinct. Further, transnational and supranational context of inescapable globalized processes are of the great significant domains to this concern too. In this regard, rendering with some common conceptual references of intellectually satisfying literatures, this paper aims to have recourse in searching common unifying and embracing dimensions of an integral nationalism, a collective overarching Nepalese identity woven within a common national sovereignty through which all the differences and commonalities can be shared, practiced and recognized so that may create pressure to sublimate bare political yearnings and therefore, pleads for the people in public-spheres and the social scientists, intellectuals to broach and share their views.